2020
DOI: 10.1002/ece3.6298
|View full text |Cite
|
Sign up to set email alerts
|

Convergent morphological responses to loss of flight in rails (Aves: Rallidae)

Abstract: The physiological demands of flight exert strong selection pressure on avian morphology and so it is to be expected that the evolutionary loss of flight capacity would involve profound changes in traits. Here, we investigate morphological consequences of flightlessness in a bird family where the condition has evolved repeatedly. The Rallidae include more than 130 recognized species of which over 30 are flightless. Morphological and molecular phylogenetic data were used here to compare species with and without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…The key question that arises is whether the separate monospecific genus Cyanolimnas is warranted? The age of the split between Cyanolimnas and Neocrex (5.9 MA) is comparatively young relative to many other Rallidae, a family that contains several old generic clades (e.g., We consider that the available molecular and morphological evidence in combination strongly supports that C. cerverai be included in either genus Neocrex Sclater & Salvin, 1869, or Mustelirallus, Bonaparte, 1856, given that its most divergent trait from either of these two, (near-)flightlessness, is well accepted to be not taxonomically informative (Olson 1973, Slikas et al 2002, Kirchman 2012, Gaspar et al 2020, Garcia-R & Matzke 2021. Although N. colombiana, an exceptionally poorly known rallid of northwestern South America and easternmost Panama, has yet to be sampled genetically, to date there is no indication that it is not very closely related to N. erythrops (Wetmore 1967, Olson 1973, Taylor 1996.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The key question that arises is whether the separate monospecific genus Cyanolimnas is warranted? The age of the split between Cyanolimnas and Neocrex (5.9 MA) is comparatively young relative to many other Rallidae, a family that contains several old generic clades (e.g., We consider that the available molecular and morphological evidence in combination strongly supports that C. cerverai be included in either genus Neocrex Sclater & Salvin, 1869, or Mustelirallus, Bonaparte, 1856, given that its most divergent trait from either of these two, (near-)flightlessness, is well accepted to be not taxonomically informative (Olson 1973, Slikas et al 2002, Kirchman 2012, Gaspar et al 2020, Garcia-R & Matzke 2021. Although N. colombiana, an exceptionally poorly known rallid of northwestern South America and easternmost Panama, has yet to be sampled genetically, to date there is no indication that it is not very closely related to N. erythrops (Wetmore 1967, Olson 1973, Taylor 1996.…”
Section: Discussionmentioning
confidence: 90%
“…We consider that the available molecular and morphological evidence in combination strongly supports that C. cerverai be included in either genus Neocrex Sclater & Salvin, 1869, or Mustelirallus , Bonaparte, 1856, given that its most divergent trait from either of these two, (near-)flightlessness, is well accepted to be not taxonomically informative (Olson 1973, Slikas et al . 2002, Kirchman 2012, Gaspar et al . 2020, Garcia-R & Matzke 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the differentially expressed genes (DEGs) in breast muscle also showed that changes of bone development related genes played a key role in the differences between the wild and domestic ducks. Many studies suggested that loss of ight in birds was always accompanied with limb modi cation and skeletal changes [18,19,32].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, muscle weight, wings and skeletal system are also changed. For instance, a ightless steam duck (T. patachonicus) was founded that wing loading, humerus length, radius length, and ulna length was signi cantly changed compare to their ight relatives [18], and the similar trend also occurs in ightless rails [19].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, multiple independent transitions to flightlessness within the same crown bird subclade are not uncommon. For example, flightlessness has arisen dozens of times in Rallidae among island-dwelling taxa [52,53]. According to some recent molecular topologies, transitions to flightlessness arose a minimum of six times in palaeognaths, and transitions to gigantism a minimum of five [41,45].…”
Section: Introductionmentioning
confidence: 99%